NUMERICAL SIMULATIONS OF EROSION IN 90-DEGREE ELBOW DUE TO FINE PARTICLES TRANSPORTED IN ANNULAR FLOW REGIME - TRAN, NGO NGUYET (2018)
Erosion due to solid fine particles presents one of the greatest threats to oil and gas flow assurance and consequently impacting material selection and wall thickness design.